FRAUD DIAMOND DALAM FINANCIAL STATEMENT FRAUDFRAUD DIAMOND DALAM FINANCIAL STATEMENT FRAUD - Siddiq, Faiz Rahman; Hadinata, Sofyan (BISNIS, 2016)
The financial statements will become more qualified in thepresentation if the presentation is based on qualitativeelements, among others: easy to understand, reliable,comparable (comparable), and relevant. The financialstatements are presented to stakeholders, namely:management, employees, investors (shareholders), creditors,suppliers, customers, and government. Fraudulent financialreporting was a deliberate attempt by the company to deceiveand mislead the users of financial statements, especiallyinvestors and creditors, to present and manipulate the materialvalue of the financial statements. Manipulation gain profit(earnings manipulation) for the company's desire that the stockremains attractive to investors. Fraud triangle theory expressedby Cressey later developed by Wolfe and Hermanson (2009)with theory. Fraud diamond diamond fraud theory consisted offour fraud risk factors are pressure, opportunity, rationalizationand capability. Diamond fraud theory can be used in predictingfraud in proksikan with earnings management.